Conde Nast India - Mishra, Annanya (ATLAS SkillTech University, 2024)
This research paper provides an in-depth examination of my enriching internship experience at Condé Nast, a worldwide recognised media corporation recognised for its major magazines such as Vogue, Condé Nast Traveller, Architectural Digest, and GQ. The purpose of this research is to present an in-depth assessment of the internship programme, emphasizing the useful insights obtained, projects completed, and their influence on personal and professional growth. The internship at Condé Nast provided a remarkable opportunity to engage with four iconic publications: Vogue, the epitome of fashion and style; Condé Nast Traveler, a leading travel and lifestyle magazine; Architectural Digest, focusing on architecture and design; and GQ, an authority on men's fashion and culture. During the internship, I was exposed to the dynamic and fast-paced world of media and publishing, gaining hands-on experience in various facets of content creation, editorial processes, and market analysis. I got the opportunity to work directly with seasoned professionals who provided significant advice and direction during the internship. The knowledge, paired with the collaborative work atmosphere, had aided in the development of my skill set, communication ability, and project management knowledge. Furthermore, working in such a competitive and prominent setting taught me a deep respect for attention to detail and a dedication to creating high-quality material. The individual voice and style of each newspaper created various obstacles, emphasizing the significance of a customized strategy to appeal to their broad readership.
Project Report on Conde Nast India (2022-24) Under the Guidance of Dr. Parag Amin
Keywords: Condé Nast; Media Corporation; project management knowledge; communication ability